2020
DOI: 10.1186/s40517-020-00171-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thermal treatment on rock–bit interaction: a study of a combined thermo–mechanical drilling (CTMD) concept

Abstract: The construction of wells, for example to extract oil, gas or heat from underground reservoirs requires substantial financial investments, which are mainly related to the involved drilling operations (Tester et al. 2006;Akin and Karpuz 2008;Petty et al. 2009;Lukawski et al. 2014;Diaz et al. 2017). Additionally, the current trend of accessing deeper underground resources poses challenges for the overall project economics, as the costs increase exponentially with well depth (Fitzgerald 2013;Abdo and Haneef 2013;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…A decrease in the DRI with temperature for watercooled samples coincided with a marginal porosity and a volume decrease at 200 • C [51]. This effect is related to the closure of pores and fissures by thermal dilation of calcite [16,52] and is a factor that hinders penetration [37]. Thus, closure of pores and fissures is behind a decrease in thermal drilling performance at low temperatures for water-cooled samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in the DRI with temperature for watercooled samples coincided with a marginal porosity and a volume decrease at 200 • C [51]. This effect is related to the closure of pores and fissures by thermal dilation of calcite [16,52] and is a factor that hinders penetration [37]. Thus, closure of pores and fissures is behind a decrease in thermal drilling performance at low temperatures for water-cooled samples.…”
Section: Discussionmentioning
confidence: 99%
“…Rossi et al [35] explored the feasibility of thermally assisted drilling using a flame jet to achieve high local heating rates, and determined a drop of 30% in UCS for temperatures up to 600 • C. Jamali et al [36] used high powered laser technology to decrease rock strength, drilling strength, and fracture toughness at rates of 60% in granite and 30% in sandstone. Rossi et al [37] studied a combined thermo-mechanical drilling (CTMD) using a flame jet and stated that the thermal treatment of rocks causes extensive thermally induced cracks in granite and sandstone, which significantly enhances the penetration performance of cutting tools. Later, Rossi et al [38][39][40] implemented this technology in the field and demonstrated an increase in the removal performance in hard rocks by up to a factor of three when compared to conventional drilling methods, and concluded that integration of thermal assistance to conventional rotary drilling constitutes an interesting approach to facilitate the drilling process.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma Pulse Geo Drilling (PPGD) is a novel contactless drilling technology, which uses high-voltage electric pulses to break away the rock, without relying on mechanical abrasion (e.g., [5,[8][9][10][11][12][13][14][15][16][17][18][19]). Thus, PPGD is part of a class of new "contactless" drilling technologies, which also includes thermal spallation (e.g., [6,[20][21][22][23][24][25][26][27][28][29][30][31][32]) and water jet drilling (e.g., [33][34][35][36][37]) and laser drilling (e.g., [38][39][40][41][42][43]) to name only some. PPGD has been given various names in the literature, including Electropulse Drilling, Plasma Channel Drilling, and Electric Impulse Drilling.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of nominal tensile strength is associated with the numbers of induced influencing rock abrasivity (Ji et al, 2021;Rossi et al, 2020b). For instance, the noncontact flame-jet spallation technique and flame-assisted rotary drilling can improve the drilling performance by thermally weakening the rock prior to the rock removal (Rossi et al, 2018 and.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, rock abrasivity is the function of temperature from multi-filed, including the geothermal condition, thermal assist operation, and varying temperature gradient with distance from the rock surface (Rossi et al, 2020b;Rathnaweera et al, 2018). Therefore, it is worthy to evaluate the rock abrasivity at extreme temperatures followed by different cooling treatments.…”
Section: List Of Tablesmentioning
confidence: 99%